National policy for the integral health of the black population (PNSIPN) and the adherence of the black population to health services (International Seven Journal of Multidisciplinary, 2023)
Although the black population represents the majority of the inhabitants of the country, this group still deals with the most diverse types of discrimination and racial inequality, and when it comes to health, this reality is no different. Later the Ministry of Health recognized that these differences were also an aggravating factor in the health of this population, thus using studies to highlight these inequalities and creating in 2009 the National Policy of Integral Health of the Black Population (PNSIPN).It is necessary the production of scientific knowledge about the health of the black population for the continuous improvement of the PNSIPN, as a way also to overcome racism and denounce the violations of rights to health and life, so this study seeks to highlight how the adherence of the black population to health services. In this study we chose to be a qualitative literature review in order to identify productions on the theme PNSIPN and the adherence of the black population to health services. Research shows that racist attitudes in health services are not sporadic facts, it is something recurrent and that make up a vicious circle that separates people, and dehumanizes them by keeping them away from their rights. In summary this research contributes to consolidate the scientific knowledge produced by Brazilian researchers about the health of the black population and reinforce this theme in order to be listed in all possible places, until the whole society understands how harmful racial inequality is, and in a rational way face it and extinguish it. DOI: 10.56238/isevmjv2n1-008